Vasopressin Initiation Timing and In-Hospital Mortality in Septic Shock: An Observational Study of Large Public Databases - Gretchen L. Sacha, PharmD; Abhijit Duggal, MD, MPH, MSc; Anita J. Reddy, MD, MBA; Lu Wang, MS; Seth R. Bauer, PharmD (Critical Care Explorations)
IMPORTANCE:. Vasopressin is used in one-third of patients with septic shock to augment hemodynamics and reduce overall catecholamine exposure. However, the optimal clinical context in which to initiate vasopressin is unknown. OBJECTIVES:. To determine the association between norepinephrine-equivalent dose, lactate concentration, and time duration from shock onset at vasopressin initiation with in-hospital mortality DESIGN, SETTING, AND PARTICIPANTS:. Retrospective, observational evaluation utilizing Medical Information Mart for Intensive Care-IV and electronic ICU Collaborative Research Database databases of adult patients with septic shock based on modified Sepsis-3 criteria receiving continuous infusion catecholamines. MAIN OUTCOMES AND MEASURES:. The associations of norepinephrine-equivalent dose, lactate concentration, and time duration from shock onset at vasopressin initiation with in-hospital mortality were evaluated with multivariable regression models. RESULTS:. In total, 1409 patients from 209 hospitals were included. At vasopressin initiation patients had a median (interquartile range) norepinephrine-equivalent dose 28.4 µg/min (16.4–42.6 µg/min), lactate concentration 3.7 mmol/L (2.5–6.2 mmol/L), and 5.6 hours (2.0–13.5 hr) had elapsed since shock onset. All three variables of interest were associated with in-hospital mortality. Three restricted cubic spline knots were identified where the relationship between norepinephrine-equivalent dose and in-hospital mortality changed substantially: 9, 28, and 72 µg/min. The odds of in-hospital mortality increased by 90% and 3.9-fold when comparing vasopressin initiation at norepinephrine-equivalent doses of 28 µg/min and 72 µg/min to 9 µg/min, respectively (adjusted odds ratio [OR], 1.90 [95% CI, 1.49–2.41] and 3.93 [95% CI, 2.74–5.64]). The odds of in-hospital mortality increased by 16% for every mmol/L in the lactate concentration at vasopressin initiation (adjusted OR, 1.16 [95% CI, 1.11–1.21]). Finally, the odds of in-hospital mortality increased by 3% for every hour in the time duration from shock onset to vasopressin initiation (adjusted OR, 1.03 [95% CI, 1.01–1.04]). CONCLUSIONS AND RELEVANCE:. Earlier adjunctive vasopressin initiation may decrease mortality in patients with septic shock.